The Influence of the Design of Nursing Care Documentation Design SDKI, SLKI, SIKI (3S) in Hospital Management Information Systems on Nurse Satisfaction at Dian Harapan Jayapura Hospital - Marthen Sege; Blacius Dedi; Isak Jurun Hans Tukayo (Syntax Corporation Indonesia, 2022)
The Service is required to be part of the hospital in implementing the documentation of nursing care using computerization. Patients in hospitals often feel dissatisfied with services because nurses take too long to search for patient history data and nurses feel dissatisfied in paper-based documentation which makes the workload increase. The purpose of this study was to design a nursing care documentation design in the 2000s SDKI, SLKI, SIKI (3S) in hospital management information systems on nurse satisfaction. The research method used a research and development design as well as descriptive observational cross sectional with a total sampling technique of 74 nursing respondents at Dian Harapan Jayapura Hospital and analyzed using simple regression analysis. The results showed that 73% of the 3-S nursing care documentation design in SIMRS was in the good category and 77% of nurses were satisfied with the 2000s nursing care documentation design in SIMRS and a significant p-value (0.000) which means that there is an effect of 30.8 % between the design of the 3S nursing care documentation in SIMRS and the satisfaction of nurses at Dian Harapan Jayapura Hospital. It can be said that by increasing the resulting information system, the satisfaction of nurses as users is getting better. It is recommended to hold socialization, training and policy realization for nurses documenting 3S nursing care in SIMRS.